Fiscal rule and public investment in Chile - J. Rodrigo Fuentes S. M.; Klaus Schmidt-Hebbel; Raimundo Soto (Inter-American Development Bank (IDB), 2021)
This paper reviews the design and operation of the Chilean fiscal rule in the past 30 years. Using different empirical approaches, we assess its impact on fiscal procyclicality, public debt, and public investment. While there has been substantial progress in building a modern institutional framework for fiscal policy, we find that the rule is incomplete in two dimensions: it lacks an escape clause, and it needs to supplement the budget balance rule with a debt rule. The former is seen in the pervasive inability of the authorities to steer fiscal accounts back to their long-term sustainable path after the rule was breached the rule in 2009. The latter issue is illustrated by the speedy build-up of the public debt as a result of the need to finance fiscal deficits. We do not find, nevertheless, a negative impact of the rule on public investment. We propose reforms to improve on transparency and accountability, as well as to supplement the rule with escape clauses and a debt anchor.
Keywords: E61; E62; H54; O23; 330; Fiscal rule; Public investment; Chile